2022
DOI: 10.1007/s10984-022-09440-y
|View full text |Cite
|
Sign up to set email alerts
|

Exemplification process in online education: a longitudinal study of mathematics teachers

Abstract: The examples used in the teaching–learning process of mathematics have a crucial role in fostering conceptual understanding, and some variables can affect instructors' qualified example usage. This longterm study focused on mathematics teachers’ exemplification process in face-to-face and online learning environments. In this regard, the change in examples used by mathematics teachers were evaluated in terms of content preparation and presentation during the shift from face-to-face lectures to online classes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…For our analysis, we classified mid-term studies as having at least two data collection points during two sequential pandemic learning terms (i.e., Aparicio-Chueca et al, 2023;Azorín, 2020;Cobo-Rendon et al, 2021;Holzmann-Littig et al, 2022;Jandrić et al, 2021;Lobos et al, 2022;Moorhouse & Kohnke, 2021;Nabe-Nielsen, 2022;Nikolopoulou & Kousloglou, 2022;Oliveira et al, 2022;Tulaskar & Turunen, 2022;Stewart, Baek et al, 2022;Yagmur & Koksal, 2022). There were four "long-term" studies that ultimately had one pre-COVID and two COVID data points (see Garcia et al, 2021;Reuter et al, 2021;Sevimli, 2023;Whittaker & Pearson, 2021) that we ultimately considered as mid-term studies given our focus on longitudinal data only during COVID. Based on these studies, we present the following claims, grounds, and warrants.…”
Section: Mid-term Studies: Two Sequential Learning Termsmentioning
confidence: 99%
See 2 more Smart Citations
“…For our analysis, we classified mid-term studies as having at least two data collection points during two sequential pandemic learning terms (i.e., Aparicio-Chueca et al, 2023;Azorín, 2020;Cobo-Rendon et al, 2021;Holzmann-Littig et al, 2022;Jandrić et al, 2021;Lobos et al, 2022;Moorhouse & Kohnke, 2021;Nabe-Nielsen, 2022;Nikolopoulou & Kousloglou, 2022;Oliveira et al, 2022;Tulaskar & Turunen, 2022;Stewart, Baek et al, 2022;Yagmur & Koksal, 2022). There were four "long-term" studies that ultimately had one pre-COVID and two COVID data points (see Garcia et al, 2021;Reuter et al, 2021;Sevimli, 2023;Whittaker & Pearson, 2021) that we ultimately considered as mid-term studies given our focus on longitudinal data only during COVID. Based on these studies, we present the following claims, grounds, and warrants.…”
Section: Mid-term Studies: Two Sequential Learning Termsmentioning
confidence: 99%
“…While we identified 14 studies that were long-term in nature collecting data over three or more semesters, four of these were comparing pre-COVID data with COVID data (see Garcia et al, 2021;Reuter et al, 2021;Sevimli, 2023;Whittaker & Pearson, 2021), leaving 10 longterm studies (e.g., Berger et al, 2021;Bettencourt et al, 2022;Cicha et al, 2022;Kavvadas et al, 2022;Myhre & Dewaele, 2022;Rogowska et al, 2021;Senior, 2022;Shiratori et al, 2022;Stracke et al, 2022) that spanned at least three consecutive semesters and in one case, four (see . All of these studies documented little to no meaningful change over the long-term despite educators and students having experience with and the ability to plan for remote teaching, and institutions committing to the practice for consistency and stability.…”
Section: Long-term Studies: Three or More Sequential Learning Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the widespread use of online or hybrid teaching models, OLEs have started to replace face-to-face classes. Offering more flexible and comfortable learning experiences, opening channels for synchronous and asynchronous communication and interaction, allowing for greater collaboration and interaction with peers, providing access to learning resources in various forms, and promoting authentic and embedded learning are some of the benefits of OLEs (Albrahim, 2020;Dhakal & Sharma, 2016;Fermín -González, 2019;Mueller & Strohmeier, 2011;Sevimli, 2023;Trenholm et al, 2011). Furthermore, it has been stated that OLEs have the potential to support access to classes for learners who cannot attend face-to-face classroom environments due to socio-economic, academic or health problems (Bell & Federman, 2013;Dhakal & Sharma, 2016).…”
Section: Online Learning Environmentsmentioning
confidence: 99%
“…Research conducted into this will both reveal the experiences of teachers in the new environment and reflect the technological pedagogical competencies needed in online education environments. Because of the reflections of current teaching practices, mathematics teachers can better understand their role in online classrooms (Baran, Correia & Thompson, 2011;Sevimli, 2023). In addition, information about the online teaching process and the technological/pedagogical aspect of online teaching will be offered in this study and thus awareness of the possible limitations of online teaching will be shown.…”
Section: Introductionmentioning
confidence: 99%